2008
DOI: 10.1371/journal.pmed.0050008
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Rapamycin in a Phase I Trial for Patients with Recurrent PTEN-Deficient Glioblastoma

Abstract: BackgroundThere is much discussion in the cancer drug development community about how to incorporate molecular tools into early-stage clinical trials to assess target modulation, measure anti-tumor activity, and enrich the clinical trial population for patients who are more likely to benefit. Small, molecularly focused clinical studies offer the promise of the early definition of optimal biologic dose and patient population.Methods and FindingsBased on preclinical evidence that phosphatase and tensin homolog d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
444
2
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 521 publications
(469 citation statements)
references
References 51 publications
19
444
2
4
Order By: Relevance
“…We have previously shown that feedback activation of Akt signaling significantly inhibits the clinical efficacy of rapamycin (10). This appears to be mediated through S6K1 inhibition and up-regulation of receptor tyrosine kinases or their substrates (11,15), although the factors that mediate feedback activation in patients have yet to be fully elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that feedback activation of Akt signaling significantly inhibits the clinical efficacy of rapamycin (10). This appears to be mediated through S6K1 inhibition and up-regulation of receptor tyrosine kinases or their substrates (11,15), although the factors that mediate feedback activation in patients have yet to be fully elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…In glioblastoma, attempts to target mTOR with rapamycin and its analogues have largely failed to show efficacy (7)(8)(9), mediated by difficulty in fully inhibiting mTORC1 signaling and by emergence of a feedback loop, that activates pro-growth, pro-survival Akt signaling (10). Rapamycin analogues also activate MAPK through a PI3K-dependent mechanism in other cancer types, suggesting additional potential mechanisms of clinical resistance and raising the need for alternative strategies to target mTOR signaling in patients (11).…”
mentioning
confidence: 99%
“…Using pre-and post-treatment tissue sampling they showed that treatment with rapamycin could inhibit mTORC1 activity within tumors of a subset of patients and this correlated with reduced proliferation (Cloughesy et al, 2008). However, in half of the patients, rapamycin treatment led to increased levels of phosphorylated AKT and shorter time to tumor progression.…”
Section: Preclinical and Clinical Studies Of Pi3k Inhibitionmentioning
confidence: 99%
“…In addition, inhibition of mTORC1 by rapamycin and its analogues has been shown to result in hyperactivation of AKT through the release of negative feedback loop between S6K1 and IRS-1 (18). Indeed, Cloughesy and colleagues have recently shown that hyperactivation of AKT following rapamycin treatment was associated with shorter time to progression in PTEN-deficient glioblastoma patients, suggesting that TORC1-specific inhibition and associated AKT activation limits anticancer activity (19). Consequently, intense efforts are now underway to develop inhibitors of the PI3K/AKT/mTOR pathway, including ATP-competitive small molecule mTOR kinase inhibitors targeting both mTORC1 and mTORC2 (20).…”
mentioning
confidence: 99%